Highly spatial–temporal electrochemical profiling of molecules trafficking at a single mitochondrion in one living cell - Kang Liu; Lina Wu; Yuanyuan Ma; Desheng Chen; Rujia Liu; Xiaobo Zhang; Dechen Jiang; Rongrong Pan (Proceedings of the National Academy of Sciences, 2025)
Simultaneous profiling of multiple molecules trafficking at a single organelle and the surrounding cytosol within a living cell is crucial for elucidating their functions, necessitating advanced techniques that provide high spatial–temporal resolution and molecule specificity. In this study, we present an electrochemical nanodevice based on a θ-nanopipette designed to coanalyze calcium ions (Ca 2+ ) and reactive oxygen species (ROS) at a single mitochondrion and its surrounding cytosol, thereby enhancing our understanding of their trafficking within the signaling pathways of cellular autophagy. Two independent nanosensors integrated within the channels of the θ-nanopipette spatially isolate a single target mitochondrion from the cytosol and simultaneously measure the release of Ca 2+ and ROS with high spatial–temporal resolution. Dynamic tracking reveals the direct trafficking of lysosomal Ca 2+ to the mitochondrion rather than to the cytosol, which triggers ROS-induced ROS release within the mitochondria. Furthermore, highly temporal and concurrent observations revealed a second burst of Ca 2+ in both the mitochondrion and the cytosol, which is not consistent with the change in ROS. These dynamic data elucidate the potential role of a beneficial feedback loop between the Ca 2+ signaling pathway and the subsequent generation of mitochondrial ROS in ML-SA-induced autophagy. More importantly, this innovative platform facilitates detailed profiling of the molecular interactions between trafficking molecules within the mitochondria and the adjacent cytosolic environment, which is hardly realized using the current superresolution optical microscopy.